A Randomized Crossover Trial on the Acute Cardiovascular Demands During Flywheel Exercise - Zubac, Damir; Ivančev, Vladimir; Valić, Zoran; Pišot, Rado; Meulenberg, Cécil J. W.; Trozić, Irhad; Goswami, Nandu; Šimunič, Boštjan (Frontiers in Physiology, 2021)
In a randomized crossover trial, we investigated the effects of variable load, high-intensity exercise on cardiovascular response in healthy participants of a wide-age range (20 to 55 y). 30 participants of both sexes (37% women) underwent a detailed medical examination and their maximal oxygen uptake was determined. They performed a squat exercise on a flywheel ergometer set at three randomly assigned moments of inertia, while the cardiovascular response was continuously recorded via Task force monitor. Compared to resting values, robust rises in mean arterial pressure, were observed during all three flywheel loads, reaching the highest value of 179±4 mmHg (p=.001) during the highest load. In parallel, the cardiac index was two-fold greater during all flywheel loads compared to rest, and at high load exclusively the total peripheral resistance increased by 11% (p=.001). The rise in heart rate compensated for a load-dependent drop in the stroke index. In our study population, no correlations were observed between the relative increase in mean arterial pressure and the participants’ age for the three flywheel loads. But the larger moments of inertia imposed a substantial burden to the cardiovascular system, without apparent associated age-differences of the relative magnitude of mean arterial pressure rise throughout the exercise.